Normal and oblique penetration of woven CFRP laminates by a high velocity steel sphere - Hazell, Paul J.; Kister, Guillaume; Stennett, Christopher; Bourque, P.; Cooper, G. (Elsevier, 2008)
In this research, two thicknesses of a woven CFRP laminate have been subjected to impact by a steel sphere in a velocity regime ranging from 170 to 374 m/s. Impact and penetration of targets at normal and oblique incidence were studied using high speed video. For the normal incidence targets at the higher velocities of impact, a conical mass of laminate was ejected ahead of the projectile. Furthermore, despite the energy transferred to the plate increasing with impact energy, the degree of delamination in the thicker targets decreased indicating a change in projectile penetration mechanism. Eventually, the degree of delamination in the thicker targets appeared to approach an asymptotic level whereas for the thinner targets the degree of delamination appeared constant regardless of impact energy. For oblique targets, more of the kinetic energy was transferred from the projectile when compared to the same thickness of target that had been subjected to a normal incidence impact. However, this was merely due to a geometrical effect. Further, thicker panels appeared to behave more efficiently by absorbing more kinetic energy per effective linear thickness at the lower impact energies where petalling is a dominant factor in the penetration. This advantage appeared to disappear as the impact energy was increased.
Keywords: penetration mechanics; spherical projectiles; failure mechanisms; Carbon-fibre-reinforced-polymer